Kawasaki disease following administration of 13-valent pneumococcal conjugate vaccine in young children - Yung, Chee Fu (2020)
Kawasaki disease (KD) is a systemic vasculitis mainly affecting young children and the leading cause of acquired heart disease in developed countries. We performed a self-controlled case series analysis to investigate the association between PCV13 and KD. All hospitalized KD cases <2 y old from our hospital in Singapore from 2010 to 2014 were included. Complete KD cases were classified based on the definitions of the American Heart Association. During the study period, 288 KD cases were identified. A total of 21 KD cases (12 were classified as Complete KD) had date of onset within the risk interval of day 1 to day 28 post PCV13. The age-adjusted Relative Incidence (RI) for KD following PCV13 dose 1, dose 2 and dose 3 were 1.40 (95%CI, 0.72 to 2.71), 1.23 (95% CI, 0.62 to 2.44) and 0.34 (95% CI, 0.08 to 1.40) respectively. There were seven Complete KD cases with onset during the risk interval after dose 1 of PCV13 (age-adjusted RI 2.59, 95%confidence interval (CI), 1.16 to 5.81). We did not detect a significant increased risk for overall KD among PCV13 recipients. However, a significant association between PCV13 and Complete KD was noted following receipt of the first dose of PCV13.